2009
DOI: 10.1254/jphs.09r02cr
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and Neuropsychiatric Therapeutics: Neuroplasticity via Glycogen Synthase Kinase-3β, β-Catenin, and Neurotrophin Cascades

Abstract: Abstract. Mood disorders are not merely attributed to the functional defect of neurotransmission, but also are due to the structural impairment of neuroplasticity. Chronic stress decreases neurotrophin levels, precipitating or exacerbating depression; conversely, antidepressants increase expression of various neurotrophins (e.g., brain-derived neurotrophic factor and vascular endothelial growth factor), thereby blocking or reversing structural and functional pathologies via promoting neurogenesis. Since the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 109 publications
3
86
1
1
Order By: Relevance
“…98 patients met criteria for assignment to one of the 4 treatment groups (phase II): 1) Lithium-augmentation (LiAugm), 2) switch of antidepressants (AD-Switch), 3) combination of antidepressants (AD-Comb), 4) augmentation with SGA (SGA-Augm). Criteria for enrolment into analysis were: patients had to have an adequate antidepressant monotherapeutic treatment in phase I according to duration (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) To assess the severity of depressive symptoms, clinician-rated and self-rating instruments were used at admission and at discharge (t1 and t2). Treatment groups were as heterogeneous as they normally appear in clinical practice.…”
Section: Assignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…98 patients met criteria for assignment to one of the 4 treatment groups (phase II): 1) Lithium-augmentation (LiAugm), 2) switch of antidepressants (AD-Switch), 3) combination of antidepressants (AD-Comb), 4) augmentation with SGA (SGA-Augm). Criteria for enrolment into analysis were: patients had to have an adequate antidepressant monotherapeutic treatment in phase I according to duration (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) To assess the severity of depressive symptoms, clinician-rated and self-rating instruments were used at admission and at discharge (t1 and t2). Treatment groups were as heterogeneous as they normally appear in clinical practice.…”
Section: Assignmentmentioning
confidence: 99%
“…A possible conclusion could be that patients who do not respond to substances with this mode of functioning do have a higher benefi t with medications of a diff erent mode of action. Possible explanations of superiority of Li-Augm compared to AD-Switch or AD-Comb include the diversity of pharmacological functioning: Lithium infl uences the neurotransmittersystem on the level of second messengers and gene-regulation [ 31 ] . Previous research has also focused on possible antidepressant eff ects of SGAs particularly on the multiple eff ects of those substances on diff erent neurotransmitters and their second messengers.…”
mentioning
confidence: 99%
“…Lithium also increases Aktmediated phosphorylation of GSK3␤, which inhibits the activity of the enzyme. Altered levels of GSK3␤ and its target ␤-catenin are associated with various neuropsychiatric disorders and neuropsychiatric drugs (Wada, 2009). Moreover, GSK3␤ inhibitors have been shown to have antidepressant and anti-manic-like activity (Kaidanovich-Beilin et al, 2004;O'Brien et al, 2004;Gould et al, 2006).…”
Section: Vgf Contributes To Some Of the Behavioral Effects Of Lithiummentioning
confidence: 99%
“…Glycogen synthase kinase-3b (GSK-3b) is a serine threonine kinase that plays a key role in gene expression regulation (Wada, 2009;Hur and Zhou, 2010). Recently, Li et al demonstrated the involvement of GSK-3b in the recovery after CNS ischemic insults (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%